Who and how? Preservice teachers as active agents developing professional identities. (April 2016) - Ruohotie-Lyhty, Maria; Moate, Josephine
Abstract: This study is part of an ongoing action research project with preservice class teachers in Finland. The study aims to better understand the forms agency takes in preservice teachers' professional identity development. Through the dialogical analysis of student assignments, this study outlines how student teachers are active within their own development and the way in which experiences are drawn on as preservice teachers exert their identity-agency. The results of this study provide a relational picture of identity development highlighting the way in which identity-agency is contextualized, potentially nourished by the relationships between self and other and dependent on experience. Highlights: The identity development of eight preservice teachers over a two year period. An investigation into the different forms of agency in identity development. Exploration of preservice teachers' activity within their own development. Seeking understanding of experiences that support identity awareness. Critical consideration of the mediating role of identity-agency as a theoretical concept.